The Search for Major Plagge : the Nazi Who Saved Jews (Expanded Edition). - Good, Michael (Fordham University Press, 2006)
When The Search for Major Plagge was published last spring, the world finally learned about a unique hero?and about one American doctor?s extraordinary journey to tell Karl Plagge?s story. Part detective story, part personal quest, Michael Good?s book is the story of the German commander of a Lithuanian work camp who saved hundreds of Jewish lives in the Vilna ghetto?including the life of Good?s mother, Pearl. Who was this enigmatic officer Pearl Good had spoken of so often?After five years of research?interviewing survivors, assembling a team that could work to open German files untouched for.